HAPPILY N'EVER AFTER - Williams, John H.; Moreland, Robert (Screenwriter); Kaplan, Yvette; Bolger, Paul J.; Gellar, Sarah Michelle, 1977-; Prinze, Freddie, Jr; Dick, Andy, 1966-; Shawn, Wallace; Warburton, Patrick; Carlin, George; Weaver, Sigourney, 1949- (Lionsgate, 2007)
Sleeping Beauty, Rapunzel and Jack are all about to live happily ever after when the balance between good and evil gets thrown out of whack. It's up to Ella to save the day by taking on her power-hungry stepmother, Frieda. This time, Ella will have to do it without her Prince Charming as she joins forces with an unlikely army of dwarves, fairies, and the Wizard's bumbling assistants, Mambo and Munk.